Prevalence of urinary tract infection in pregnant women in terms of various risk factors of Dhaka city - Ema, Eshrat Islam (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2018.